2013
DOI: 10.1155/2013/752150
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective Activity ofMurraya exoticathrough Inhibitingβ-Catenin Signaling Pathway

Abstract: Osteoarthritis (OA) is a degenerative joint disease that affects millions of people. Currently, there is no effective drug treatment for it. The purpose of this study is to investigate the chondroprotective effects of Murraya exotica (L.) on OA. The rat OA models were duplicated to prepare for separating OA chondrocytes, synovial fluid (SF), and serum containing M. exotica (50 mg/kg, 100 mg/kg, and 200 mg/kg), M. exotica showed the activity of decreasing the contents of TNF-α and IL-1β in SF and the chondrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The injection administration of resveratrol can significantly upregulate SIRT1 expression and downregulate the HIF-2 α expression, leading to suppression of iNOS and MMP-13 expression [ 110 ]. Our research group shows that Murraya exotica (L.) can dose-dependently downregulate the mRNA and protein expression of β -catenin and COX-2, inhibit the levels of TNF α and IL- β in synovial fluids, and decrease the chondrocytes apoptosis [ 111 ].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The injection administration of resveratrol can significantly upregulate SIRT1 expression and downregulate the HIF-2 α expression, leading to suppression of iNOS and MMP-13 expression [ 110 ]. Our research group shows that Murraya exotica (L.) can dose-dependently downregulate the mRNA and protein expression of β -catenin and COX-2, inhibit the levels of TNF α and IL- β in synovial fluids, and decrease the chondrocytes apoptosis [ 111 ].…”
Section: Miscellaneousmentioning
confidence: 99%
“…Another study found that leaf extract of M exotica decreased chondrocyte apoptosis in a dose-dependent manner. 27 Although the plant extracts used in this study did not protect MDA-MB-231 cells from apoptosis, they did not cause much damage to the breast cancer cells. Studies have been conducted to demonstrate efficient cytotoxicity against tumor cells by coumarins from M exotica.…”
Section: Discussionmentioning
confidence: 66%
“…The nutrients found in the curry leaves are carbohydrates, fiber, calcium, iron, magnesium, copper, phosphorous, and minerals; and it also contains various vitamins like nicotinic acid and vitamin C, vitamin A, vitamin B, vitamin E, antioxidants, plant sterols, amino acids, glycosides, and flavonoids (Bonde, Nemade, Patel, & Patel, 2017). In India, people use the curry leaves as a flavoring agent in curries and usually which leads to the inflammation and necrosis in many pathological conditions (Dineshkumar, Mitra, & Mahadevappa, 2010;Ho et al, 2015;Paul, Bandyopadhyay, & Bhattacharyya, 2011;Wu et al, 2013). Likewise, similar condition was observed in pancreatitis.…”
Section: Discussionmentioning
confidence: 93%
“…The curry leaves exhibit potent antioxidant activity and anti‐inflammatory activity. The chemical constituents present in M. koeniggi are carbazole alkaloids, such as mahanimbine and koeiniggine, which shows antioxidant property by inhibiting the production of cytokines IL‐6 and IL‐1β by downregulation of NFκB, which leads to the inflammation and necrosis in many pathological conditions (Dineshkumar, Mitra, & Mahadevappa, ; Ho et al, ; Paul, Bandyopadhyay, & Bhattacharyya, ; Wu et al, ). Likewise, similar condition was observed in pancreatitis.…”
Section: Discussionmentioning
confidence: 99%